Inovasi Pembelajaran Pameran Seni Melalui Maket Sebagai Sarana Peningkatan Keterampilan Kuratorial Siswa Kelas XI MSB : Penelitian - Kharisma Cahya Primadani; Ike Ratnawati; Shinta Adhisti Oktarini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Art and culture education does not only emphasize the practical aspects of art-making, but also includes curatorial skills such as designing and organizing exhibitions. In practice, curatorial abilities are often underdeveloped due to the limited opportunities students have to engage directly in exhibition planning. This study aims to describe an instructional innovation in art exhibition learning through the use of exhibition mock-ups as a contextual and applicable learning medium. The research method employed is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The research subjects were 11th-grade art students at SMAN 4 Malang who were involved in creating mock-ups and planning an art exhibition. The findings indicate that the use of mock-ups as a learning medium helps students concretely understand curatorial concepts in art exhibitions. Students also demonstrated improvement in their ability to write exhibition proposals and activity reports. This innovation has proven effective in providing meaningful learning experiences in the development of students’ curatorial skills.